2021
DOI: 10.1016/j.jamda.2020.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Rates of PRN Medication Administration in Australian Residential Aged Care

Abstract: Objective: To investigate administration of pro re nata (PRN) medications and nurse-initiated medications (NIMs) in Australian aged care services over a 12-month period. Design: Twelve-month longitudinal audit of medication administrations. Setting and participants: Three hundred ninety-two residents of 10 aged care services in regional Victoria, Australia. Methods: Records of PRN and NIM administration were extracted from electronic and hard copy medication charts. Descriptive statistics were used to calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…9 Similarly, recent research using electronic administration data identified a more than 3-fold variation in rate of PRN administration per resident-month across 10 aged care homes operated by the same provider. 16 Reducing the current siloed nature of the different administrative data sets from the same aged care provider by merging them together delivers further useful information to support decision-making and quality improvement programs specific to an aged care organisation, home or individual. For example, linking health conditions documented in one part of the information system to the eMAR through unique identifiers allows an assessment of the use of medication for specific conditions and enables risk adjustment.…”
Section: More Granular Informationmentioning
confidence: 99%
“…9 Similarly, recent research using electronic administration data identified a more than 3-fold variation in rate of PRN administration per resident-month across 10 aged care homes operated by the same provider. 16 Reducing the current siloed nature of the different administrative data sets from the same aged care provider by merging them together delivers further useful information to support decision-making and quality improvement programs specific to an aged care organisation, home or individual. For example, linking health conditions documented in one part of the information system to the eMAR through unique identifiers allows an assessment of the use of medication for specific conditions and enables risk adjustment.…”
Section: More Granular Informationmentioning
confidence: 99%
“…26,27 It is commonly used for various types of medications to relieve patients' physical and psychological suffering. Besides acetaminophen and opioids for pain relief, 28 psychotropic and psycholeptic medications are more commonly prescribed and administered as PRN to older patients with long-term mental health conditions, [29][30][31][32] but the clinical effectiveness of this style of medication use in comparison with other prescription and administration styles of medication has remained unexplored and needs further research. 33 Inappropriate use of PRN medications can extend the duration of hospitalisation in long-term healthcare settings and hinder the smooth transition of care for older people with chronic health conditions to their own home.…”
Section: Prn Medicines Management In Home Carementioning
confidence: 99%
“…52 A related controversial area is how much to encourage or discourage pro re nata (PRN) administration in residential long-term care settings, which is discussed in the context of results of a multifacility survey conducted in Australia. 53 With the COVID-19 pandemic having particularly devastating effects in long-term care communities, a particularly urgent emerging need is to better understand whether and how to effectively treat early COVID-19 infection in older persons, to prevent disease progression and reduce the probability of long-term consequences. 54 Initial enthusiasm for hydroxychloroquine and azithromycin has waned, but reports continue on other agents, including one in this month's JAMDA on metformin.…”
Section: Other Themes Around Improving the Overall Quality Of Prescribingmentioning
confidence: 99%